Diversity and Inclusion in U.S. Universities and the Pursuit of Global Leadership - Sutherland, Hannah R. (My University, 2020)
This paper will discuss why global leadership is necessary and how to begin the process of developing global leaders. In order to do this, this paper will examine universities in the United States and how they attempt to engage students in diversity, inclusion, and leadership. Some common themes will be highlighted that describe the tactics used by these universities. A connection will be made between these themes and the commonalities found among various leadership frameworks from countries and cultures around the world. The combination of these findings will form a discussion around how to develop global leaders who are prepared to lead across differences in a world that is becoming increasingly interconnected.